Vascular Streak Dieback: Penyakit Baru Tanaman Kakao di Sumatera Barat - Jumsu Trisno; Reflin Reflin; Martinius Martinius (Jurnal Fitopatologi Indonesia, 2016)
Vascular streak dieback (VSD) symptoms was reported recently in several cacao plantations in West Sumatera.  Disease incidence reached 58.82–100% with disease intensity of 24.29–44.71%.  In some cases, dead plant was also found. Fungal isolation was performed to identify the agents associated with VSD.  Plant samples showing VSD symptoms was collected from 3 locations of cacao production center in West Sumatera, i.e. Limapuluh Kota regency, Padang Pariaman regency, and Padang city.  Small pieces of leaf and twig were plated on water agar and potato dextrose agar medium for fungal isolation.  Morphology of hifa, basidiocarp, and basidiospora observed from fungi colonies indicated the presence of Ceratobasidium theobromae on infected plant samples.  This is the first report on the association of C. theobromae on cacao in West Sumatera.